Investigating the technical dimension of water supply resilience to disasters. (May 2020) - Balaei, Behrooz; Wilkinson, Suzanne; Potangaroa, Regan; McFarlane, Philip
Abstract: Water supply system functionality is vital in the aftermath of disasters. Failure of water systems can not only cause difficulties for residents and critical users, but may also affect other hard and soft infrastructures and services. Using an indicator-based model, this paper focuses on identifying the technical factors that enable water system robustness to be measured, and proposes a metric for robustness quantification. The technical variables were gathered through a comprehensive literature review, then verified and ranked through a series of interviews with water supply and resilience specialists. The study identified vulnerability, redundancy, and criticality as the most significant technical factors affecting water supply system robustness, and consequently resilience. Utilising these indicators and their influence on public water supply resilience will enable local authorities to identify existing strengths and weaknesses, and to optimise investment to obtain the best results. In addition, the proposed metric reduces the complexity and multidimensionality of factors to a measure that will support optimisation by decision makers. As a case study, the proposed indicators were employed for a hypothetical scenario earthquake in Pukerua Bay, New Zealand to show how this metric can be used to measure system robustness.